Keragaman Makrofungi di Distrik Warmare Kabupaten Manokwari, Papua Barat - Suharno Suharno; Cahya Irawan; Evie N. Qomariah; Ira A. Putri; Supeni Sufaati (Jurnal Biologi Papua, 2014)
Fungi play an important role in biogeochemical cycle, especially in decomposition of organic matter. This study was aimed to investigate the diversity of macrofungi in the Warmare District, Manokwari, Province of Papua Barat. Samples were collected at a low altitude from 15 and 290 m a.s.l. with a temperature of 20o-29oC and humidity of 83-95%. The collected samples which were documented and identified result in 62 species representing 19 families (29 genera), and those four dominant families were as follows: Polyporaceae (14 species), Agaricaceae (11 species), Tricholomataceae (9 species) and Clavariaceae (7 species).   Key words: macrofungi, diversity, Warmare District, Manokwari.